EXPLORING STUDENTS’ PERCEPTION ON DIFFICULTIES OF STRUCTURE AND WRITTEN EXPRESSION IN TOEFL TEST: A CASE STUDY - Linda Meylinda (JEELL (Journal of English Education, Linguistics and Literature), 2025)
The present study aims to explore students' perceptions of the difficulties they encounter in the "Structure and Written Expression" section of the TOEFL test at Pamulang University. This study is grounded in the context of the ongoing challenges in test preparation, particularly as students face obstacles related to grammar, sentence structure, and familiarity with the test format. The research utilizes a qualitative approach, specifically employing a case study method to gain a deep understanding of the students' perspectives. Three participants were selected based on specific criteria: Academic Performance, completion of a TOEFL course in the previous semester, and varying levels of TOEFL scores. The data collection process involved in-depth interviews with the participants, which were analyzed through thematic analysis to identify, analyze, and report patterns (themes) within their responses. This allowed for a rich, detailed interpretation of the challenges students face, focusing on their personal experiences with the "Structure and Written Expression" section. The findings from this research are expected to shed light on the common issues faced by students and suggest potential improvements in TOEFL test preparation methods. This study aims to provide valuable insights that could inform more effective instructional strategies, ultimately enhancing students' performance and confidence in the TOEFL test.